Why Dr. Hahnemann had to Discover a New, Unique, Latest Technological Method for the Preparation of Medicines and their Administration to the Patients? (Advancements in Homeopathic Research, 2022)
I am having a fear. Fear of what? What and why I am writing and reporting documented(ing) cases with reports (Laboratory & Medical Imaging Technology such as CT, CT-PT, MRI, etc.) on Homoeopathy, shall be correct and people of other system of medicine and even homoeopaths will believe and accept the results I got in cancer patients with Homoeopathy. Let me see. I hope homoeopathic community will find out the truth. These are my clinical experiences and examples by the latest, anew, unique Technology discovered by Dr. Hahnemann for the preparation of medicines and administration of medicines to patients, which are given in the 6 th edition of ORGANON OF MEDICINE.
Keywords: Hahnemann; Homoeopathy; ORGANON OF MEDICINE